Enrichment of stirred yogurts with folic acid encapsulated in pH-responsive mesoporous silica particles: Bioaccessibility modulation and physico-chemical characterization. (October 2016) - Pérez-Esteve, Édgar; Ruiz-Rico, María; Fuentes, Ana; Marcos, María Dolores; Sancenón, Félix; Martínez-Máñez, Ramón; Barat, José Manuel
Abstract: In this work, we have studied the ability of a mesoporous silica support loaded with folic acid and functionalized with amines (S1) to modulate the bioaccessibility of the vitamin after its incorporation in stirred yoghurts with different fat contents. Due to the novelty of using mesoporous silica supports in food matrixes, the influence ofS1 addition on the physicochemical, rheological and lactic acid bacteria viability of these yoghurts during 21 days of refrigerated storage at 4 °C was also evaluated. The in vitro digestion procedure showed thatS1 was capable of inhibiting the release of folic acid in acidic solution at pH 2 (stomach) and controllably release their contents in neutral pH (intestine), thereby modulating the bioaccessibility. Moreover, the physicochemical and microbiological assays revealed that enrichment generally does not alter the physicochemical properties (pH, colour, syneresis and rheology) of either type of yoghurt and does not cause any effect on lactic acid bacteria survival. Highlights: A Smart Delivery System (SDS) of FA responsible to pH changes has been prepared. Low fat and full fat yogurts have been enriched with the new SDS. The SDS was able to modulate the release kinetics of FA during the in vitro digestion. Addition of the SDS to yogurts have no impact in physico-chemical properties. Addition ofthe SDS to yogurts have no impact on of starting cultures survival.